Cold sintering of CsPbBr3 quantum dots embedded KBr ceramics for LED displays - Jie Gao; Yu Ren; Qi Ding; Peng Yan; Yongping Liu; Yunfeng Hu; Jihu Chen; Zhi Cheng; Yuchi Fan; Wan Jiang (Journal of Materiomics)
Thanks to their tunable luminescence, narrow emission range, and superior color fidelity, perovskite quantum dots (PeQDs) are widely considered as promising materials for next-generation backlight displays. However, the susceptibility to degradation and failure when exposed to ambient environment significantly hampers their widespread applications. Herein, we reported an effective strategy to encapsulate CsPbBr3 nanocrystals into robust KBr matrix via cold sintering process at 120 °C. The well prepared translucent CsPbBr3@KBr ceramic displays a narrow green photoluminescence (with a full-width at half-maximum of ∼22 nm) and an quantum yield of 73.6% with remarkable thermal stability. By incorporating red emitting K2SiF4:Mn4+ phosphor into the KBr matrix, the color gamut of the constructed white LED improves to 118% of the National Television System Committee (NTSC) standard, suggesting that the thermally robust and narrow-band green emitter holds significant promise for wide-color-gamut liquid crystal displays.